2023
DOI: 10.14414/tiar.v13i1.3213
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral finance of MSMEs in the advancement of financial inclusion and financial technology (Fintech)

Abstract: This study aims to determine empirical evidence of the effect of financial inclusion and financial technology (fintech) on the behavioral finance of MSMEs. This study uses a quantitative method with a positivist paradigm approach. The population of this study is all MSMEs in Indonesia. The sample used in this study is 205 respondents (MSME owners) from all over Indonesia. Sampling is carried out using a random technique. Data collection is carried out by distributing questionnaires, both manually and online us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…The overconfidence that results in Overconfidence Bias is one form of decision making which is influenced by emotion (emotional bias), so that investors tend to have more audacity to make a risky decision [33]. Over confidence will encourage someone to easily make a decision, without any doubts, with further consideration, so that the decision is immediately made.…”
Section: Discussionmentioning
confidence: 99%
“…The overconfidence that results in Overconfidence Bias is one form of decision making which is influenced by emotion (emotional bias), so that investors tend to have more audacity to make a risky decision [33]. Over confidence will encourage someone to easily make a decision, without any doubts, with further consideration, so that the decision is immediately made.…”
Section: Discussionmentioning
confidence: 99%
“…The rise of Islamic finance has accelerated financial inclusion in previously less deserving groups and now it is focusing on the right people. Financial inclusion is indispensable because approach to financial services is a key factor in development, growth, and opportunity (Ali et al, 2023;Danladi et al, 2023;Risman et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…MSMEs' economic role is undeniably linked to their performance and the capabilities of entrepreneurs and managers (Kyndt & Baert, 2015;Mishra & Zachary, 2015), particularly in financial management. In financial management, MSMEs, especially micro and small enterprises (UMK), exhibit distinctive characteristics as they transition from personal to corporate financial management (Risman et al, 2023). This phenomenon is a point of interest for researchers, notably those in behavioral finance.…”
Section: Introductionmentioning
confidence: 99%
“…However, specific research addressing the influence of fintech on the financial behavior of MSMEs remains relatively scarce. A limited body of research on this subject includes studies by Junianto and Kohardinata (2020), Tukan et al (2020), Anisyah et al (2021), Apriyanti andRamadita (2022), andRisman et al (2023). Junianto and Kohardinata (2020) found that fintech plays a pivotal role in shaping investment decisions, whereas Risman et al (2023) discovered that fintech positively impacts MSME financial actors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation